2003
DOI: 10.1002/ejic.200300468
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Magnetism of a New Dodecanuclear CuII Complex with Acetato and Imidazolato Bridges, Formed by Oxidation of the Chelating Ligand 1,1,7,7‐Tetrakis(imidazol‐2‐yl)‐2,6‐diazaheptane

Abstract: A novel dodecanuclear copper(II) complex [Cu 12 (tidhd) 4 -(MeOH) 8 (CH 3 COO) 8 ](MeOH) 0.8 (Htidhd = 1,1,7,7-tetrakis-(imidazol-2-yl)-2,6-diaza-1,6-heptadiene) with imidazolato and acetato bridging ligands was synthesized by reaction of polyimidazole 1,1,7,7-tetrakis(imidazol-2-yl)-2,6-diazaheptane (Htidahp) with copper acetate in a methanol solution. The complex crystallized in the triclinic space group P1 with a = 9.1204(1), b = 13.5139(2), c = 27.6925(5), α = 76.8006(6)°, β = 82.8066(7)°, γ = 76.4594(9)°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…The apical ligating atoms are an aqua oxygen atom and an anti-syn bridging carboxylate oxygen atom, respectively, at Cu1 and Cu2. The equatorial Cu-N bond lengths in the range 1.980(3)-1.992(3) Å are shorter than those in 3, but they are comparable with the corresponding ones in [Cu 12 (tidhd) 4 (CH 3 OH) 8 (CH 3 COO) 8 ](CH 3 OH) 0.8 [Htidhd = 1,1,7,7-tetrakis(imidazol-2-yl)-2,6-diaza-1,6-heptadiene], [21] whereas the basal and apical Cu-O bond lengths vary in the ranges 1.931-1.962 and 2.214-2.498(3) Å, respectively, and are longer than the corresponding ones in 3. The τ (Addison) parameters of 0.20 (Cu1) and 0.13 (Cu2) indicate more significant Figure 4.…”
Section: Compoundsupporting
confidence: 61%
See 1 more Smart Citation
“…The apical ligating atoms are an aqua oxygen atom and an anti-syn bridging carboxylate oxygen atom, respectively, at Cu1 and Cu2. The equatorial Cu-N bond lengths in the range 1.980(3)-1.992(3) Å are shorter than those in 3, but they are comparable with the corresponding ones in [Cu 12 (tidhd) 4 (CH 3 OH) 8 (CH 3 COO) 8 ](CH 3 OH) 0.8 [Htidhd = 1,1,7,7-tetrakis(imidazol-2-yl)-2,6-diaza-1,6-heptadiene], [21] whereas the basal and apical Cu-O bond lengths vary in the ranges 1.931-1.962 and 2.214-2.498(3) Å, respectively, and are longer than the corresponding ones in 3. The τ (Addison) parameters of 0.20 (Cu1) and 0.13 (Cu2) indicate more significant Figure 4.…”
Section: Compoundsupporting
confidence: 61%
“…[16,17] Interestingly, research has indicated that carboxylate groups in the above-mentioned paddle-wheel-like tetracarboxylato-bridged copper(II) dimers could be pairwise replaced by bidentate N-donor aromatic ligands to form semi-paddle-wheel (SPW) dinuclear clusters, [18][19] which, through two anti-syn bridging carboxylate oxygen atoms, could be further condensed into double-semi-paddle-wheel (DSPW) tetranuclear copper(II) clusters (Scheme 1). [20][21] Such DSPW-like tetranuclear copper(II) clusters have been found in molecular complexes; [20][21] however, it is seldom that they have been used as SBUs to construct coordination polymers. Our recent investigations show that self-assembly of Cu II ions and adipate anions in the presence of 2,2-bipyridine (bpy) or 1,10-phenanthroline (phen) provides an efficient strategy for nucleation of DSPW-like tetranuclear copper(II) clusters, which can be bridged by adipato ligands to make up porous MOFs.…”
Section: Introductionmentioning
confidence: 99%